Factors that influence behavioral intention in m-payment users in Surabaya - Evinka Dindamiatma; Antonius Setyawan; Junaid Kajee (Southeast Asian Journal of Service Management, 2025)
Many aspects of human life have shifted as a result of the rapid advancement of digital technology. Almost every aspect of human life that has been handled traditionally has begun to transition to the digital realm. In the economic field, digital payments using smartphones, also known as m-payments, are one proof of technological advances in the use of digital payments or m-payments. This study aims to analyze the factors that influence the behavioral intentions of m-payment users in Surabaya. The theory used in this study is UTAUT (Unified Theory of Acceptance and Use of Technology) with 6 independent variables (performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit), 1 mediating variable (behavioral intention), 1 dependent variable (use behavior). Respondents in this study were 150 people who were analyzed using the SEM (Structural Equation Modeling) method of data processing and testing using SmartPLS software. Based on the results of data processing, shows that performance expectations, effort expectations, social influence, facilitating conditions, hedonic motivation, and habits have a positive effect on behavioral intentions. As well as behavioral intentions have a positive effect on usage behavior.